Wire ropes with diamond beads for multi-wire machines optimization by means of DoE: Numerical models and choice of design parameters. (January 2023) - Baragetti, Sergio; Giustinoni, Marco; Ranghetti, Fabrizio
Highlights: Failure analysis and design optimization of wire ropes with diamond beads for machines used to cut blocks of hard stone. Microscopical observations were used to detect defects and cracks on the new and damaged components. Numerical FEM modelling and Design of Experiments (DoE) methods allowed to optimize the design parameters. Full scale experimental tests on real cutting machines were carried out to verify the improvement of the endurance. Abstract: This paper reports FEM model's development to optimize the stress–strain state of wire ropes used in multi-wire machines for cutting hard blocks of stone: numerical models and experimental observations were carried out with the company Pedrini SpA ad Unico Socio, located in Carobbio degli Angeli, Bergamo (Italy). The aim of the paper is to develop a numerical FEM model useful to understand the mechanical driving forces and highlight the damage mechanisms of wire ropes with diamond beads, in order to increase service life of these important cutting tools. DoE (Design of Experiments) and DACE (Design and Analysis of Computer Experiments) were applied to the numerical models to optimize the design of the wire ropes with diamond beads. Microscope observations and penetrating liquids method were used to analyze the damaged wire ropes. Fatigue, corrosion, and contact fatigue problems were observed and the effect of the centering of the beads on the wire rope was studied. Full scale and in service tests were carried out too, to better understand the behavior of the wire ropes mounted on real cutting multi-wire machines.